Visual ecology of nocturnal bees: how light intensity affects foraging activity in cambuci, a neotropical Myrtaceae - Dias, Rodolfo Liporoni (2018)
The foraging activity of day-active bees often rely on flower availability, light intensity and temperature. However, some bees developed a nocturnal habit and fly during the dusk, dawn and night. We still do not know how these bees cope with environmental factors, especially dimmer light levels, to explore flower earlier than their diurnal relatives. Given that typical bee apposition compound eyes work better in brighter environments and function in their limits in dim-light conditions, we can expect a larger dependence of light intensity for nocturnal groups. Nocturnal and crepuscular bees are frequent visitors of cambuci (Campomanesia phaea, Myrtaceae) in southeastern Brazil. We aimed to investigate how light intensity affects flower visitation of cambuci by nocturnal and crepuscular bees, also controlling for other environmental factors. We counted visits per minute along 30 nights/twilights in 33 cambuci trees from a commercial orchard, measuring the following environmental variables: light intensity, flower availability, temperature, air relative humidity and wind speed. Light intensity is the only variable that explained flower visitation of nocturnal bees in cambuci, which peaks at intermediate light levels that occur around 30 minutes before sunrise. The minimum light intensity threshold to bees start flying is of 0.00024 cd/m2, the first recorded value for nocturnal and crepuscular bees finding flowers in an agro-forest context. Our results highlight for the first time how nocturnal bees rely on light to explore resources and show that the bees light-dependent foraging activity is not always linear, as postulated by previous theoretic models. This is the first step to understand how nocturnal bees react to environmental factors. Our findings also bring concerns about possible negative effects of light pollution at night for cambuci-crepuscular bees interaction